Sistema informático para el manejo de los registros de la explotación ganadera en la finca “Santa Rosa” de la parroquia Julio Andrade. - Almeida Rosero, Daniela Alejandra (2016)
The computer system for the management of livestock logs at the Santa Rosa farm of the Julio Andrade parish is a significant application developed to contribute to the optimization of log management in the farm, examining new tools for a better management of the livestock area, which will continue to be projected to new needs. The methodology used is the classical software life cycle, which elements are: analysis, design, construction and testing. Because of this sequence of steps it is allowed to meet the requirements to ensure the quality and operation of the system from the beginning to end. It is presented a system of livestock focused on improving the quality of information entered and acquired with accurate data in the consultation, to be able to keep track of the activities that are handled inside the farm, with the help of computer tools that are immersed within this system, therefore, a reliable record of each movement is carried out within the livestock activity.